Synthesis and spectral-luminescent properties of strontium aluminates activated by bismuth and manganese ions - Shevchenko, Gvidona P.; Varapay, Natalia V.; Zhuravkov, Viktor A.; Bokshyts, Yuliya V. (Journal of the Belarusian State University. Chemistry, 2026)
Using solid-phase synthesis, SrAl2O4 + Sr3Al2O6 : Bi3+, Мn4+ luminophores were obtained. The effect of temperature and heating time on the phase composition of the final product and its spectral-luminescent properties were studied. The prospects of the method for controlling the colour characteristics of strontium aluminate samples activated by bismuth and manganese ions by varying the conditions of their synthesis was demonstrated.